2006
DOI: 10.1510/icvts.2005.125484
|View full text |Cite
|
Sign up to set email alerts
|

Does malperfusion syndrome affect early and mid-term outcome in patients suffering from acute type A aortic dissection?

Abstract: It is well known that malperfusion syndrome (MPS) increases early mortality of patients suffering from acute type A aortic dissection (AADA). The aim of the present study was to analyze the outcome of patients who survived after surgical treatment of AADA with or without MPS. Data of 227 consecutive patients, who underwent surgery for AADA, were analyzed. The impact of MPS on in-hospital data and outcome was analyzed. Quality of life (QoL), using the short form 36 health survey questionnaire (SF-36), and late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…According to literature, the incidence of brain malperfusion ranges from 7% to 14% (29,30,32,33), and significantly affected the therapeutic management. IRAD data (33) showed that nearly 1 out of 10 TAAD patients are complicated by major brain injury at onset of dissection [cerebrovascular accident (CVA) 4.7%; coma 2.9%], carrying a two or threefold higher mortality depending on presence of CVA or coma respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to literature, the incidence of brain malperfusion ranges from 7% to 14% (29,30,32,33), and significantly affected the therapeutic management. IRAD data (33) showed that nearly 1 out of 10 TAAD patients are complicated by major brain injury at onset of dissection [cerebrovascular accident (CVA) 4.7%; coma 2.9%], carrying a two or threefold higher mortality depending on presence of CVA or coma respectively.…”
Section: Resultsmentioning
confidence: 99%
“…They are most common in extensive DeBakey type I dissection (12,111). Clinically apparent malperfusion of any type increases mortality risk (107,109,111,112).…”
Section: Malperfusionmentioning
confidence: 99%
“…Although demonstration of radiological malperfusion might also be important, it is the ischemic consequences of malperfusion and end-organ dysfunction that compromise survival ( Fig. 4) (100,111,113,114). Thus, although a patient might have CT evidence of reduced true luminal (TL) innominate artery flow, the prognostic relevance of this is primarily determined (Online Table 2) by the presence of clinical neurological ischemia.…”
Section: Malperfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malperfusion syndrome (MPS) was diagnosed based on clinical symptoms pre-and perioperatively. The same definition for MPS was applied as in a recently published study from our group [15]. TND was defined as a Glasgow coma scale (GCS) value <13, these patients typically present with loss of orientation, slurred language, agitation and no clear response to commands.…”
Section: Methodsmentioning
confidence: 99%